2016
DOI: 10.1111/bju.13659
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of high‐dose‐rate brachytherapy for intermediate‐ and high‐risk prostate cancer with a median follow‐up of 10 years

Abstract: For men with intermediate- or high-risk prostate cancer features, who are considered not suitable for, or wish to avoid a radical prostatectomy, HDR prostate brachytherapy remains an appropriate treatment option. From December 2004, prevention strategies decreased the risk of post-brachytherapy urethral strictures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 21 publications
2
12
0
1
Order By: Relevance
“…Similarly our urethral stricture rate of 4.2% was in keeping with a recent review that reported crude rates from 0–14% . However, our rates were significantly lower than other Australian studies, which we attribute to three strategies. First, the precise placement of a gold fiducial marker at the very apex of the prostate under transrectal ultrasound control significantly improved the accurate delineation of the prostatic apex on CT imaging.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similarly our urethral stricture rate of 4.2% was in keeping with a recent review that reported crude rates from 0–14% . However, our rates were significantly lower than other Australian studies, which we attribute to three strategies. First, the precise placement of a gold fiducial marker at the very apex of the prostate under transrectal ultrasound control significantly improved the accurate delineation of the prostatic apex on CT imaging.…”
Section: Discussionsupporting
confidence: 91%
“…This preventative strategy widened the prostatic urethral channel and reduced the risk of subsequent urethral strictures. 12 A prior mini TURP did not increase the risk of acute or late GU toxicity in the 14 patients who underwent the procedure. The rate of late Grade 1 or greater GU toxicity was higher in the TURP cohort compared to the non-TURP cohort but this was not significant (61.5% vs. 41.5%, P = 0.18).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…В исследованиях из Японии [40,41], Испании [42,43], Австралии [44] была отмечена высокая эффектив-ОНКОУРОЛОГИЯ 1'2017 ТОМ 13 CANCER UROLOGY 1'2017 VOL. 13 Диагностика и лечение опухолей мочеполовой системы.…”
Section: оценка риска прогрессированияunclassified